A new index for the assessment of transverse sinus stenosis for diagnosing idiopathic intracranial hypertension. (3rd October 2016) - Carvalho, Gustavo Balthazar da Silveira; Matas, Sandro Luiz de Andrade; Idagawa, Marcos Hideki; Tibana, Luiz Antônio Tobaru; de Carvalho, Renato Sartori; Silva, Matheus Luis Souza; Cogo-Moreira, Hugo; Jackowski, Andrea Parolin; Abdala, Nitamar
Abstract : Background and purpose: To assess the role of MR venography (MRV) for detecting transverse sinus stenosis, to determine the importance of this finding in idiopathic intracranial hypertension (IIH), and to propose an index that contributes to this diagnosis. Materials and methods: We retrospectively assessed consecutive intracranial MRV of patients aged >18 years diagnosed with IIH according to the diagnostic criteria, between January 2010 and July 2012. The assessments were randomly analyzed by three radiologists. Stenoses in the right and left transverse sinuses were independently classified according to the following scale: 0, normal; 1, stenosis <33%; 2, stenosis 33–66%; 3, stenosis >66%; and 4, hypoplasia or agenesis. We established an index based on multiplication of the stenosis scale values for each transverse sinus. A point and range estimate of the sensitivity, specificity, and the area under the receiver operating characteristic curve was performed to obtain cut-off points to differentiate between controls and patients. Results: 63 individuals were included in this study: 32 (50.8%) diagnosed with IIH (31 (96.9%) women and 1 (3.1%) man) and 31 (49.2%) controls. According to all of the examiners, the IIH group showed a higher degree of stenosis than the control group. Index values ≥4 for a diagnosis of IIH had a sensitivity and specificity of 94.7% and 93.5%, respectively. Conclusions: MRV should be used to assess patients with suspected IIH, and bilateral transverse sinus stenosis should be considered for the diagnosis. The stenosis classifying index proposed here is a fast and accessible method for diagnosing IIH.